Incidence and prognostic impact of cytogenetic aberrations in patients with systemic mastocytosis - Naumann, Nicole; Jawhar, Mohamad; Schwaab, Juliana; Kluger, Sebastian; Lübke, Johannes; Metzgeroth, Georgia; Popp, Henning; Khaled, Nada; Hofmann, Wolf-Karsten; Reiter, Andreas; Fabarius, Alice (Genes, chromosomes & cancer, 2018)
The clinical behavior of systemic mastocytosis (SM) is strongly associated with activating mutations in KIT (D816V in >80% of cases), with the severity of the phenotype influenced by additional somatic mutations, for example, in SRSF2, ASXL1, or RUNX1. Complex molecular profiles are frequently associated with the presence of an associated hematologic neoplasm (AHN) and an unfavorable clinical outcome. However, little is known about the incidence and prognostic impact of cytogenetic aberrations. We analyzed cytogenetic and molecular characteristics of 109 patients (KIT D816V+, n = 102, 94%) with indolent (ISM, n = 26) and advanced SM (n = 83) with (n = 73, 88%) or without AHN. An aberrant karyotype was identified in SM-AHN (16/73, 22%) patients only. In patients with an aberrant karyotype, additional somatic mutations were identified in 12/16 (75%) patients. Seven of 10 (70%) patients with a poor-risk karyotype, for example, monosomy 7 or complex karyotype, and 1/6 (17%) patients with a good-risk karyotype progressed to secondary acute myeloid leukemia (n = 7) or mast cell leukemia (n = 1) within a median of 40 months (range 2-190, P = .04). In advanced SM, the median overall survival (OS) of poor-risk karyotype patients was significantly shorter than in good-risk/normal karyotype patients (4 vs 39 months; hazard ratio 11.7, 95% CI 5.0-27.3; P < .0001). Additionally, the shortened OS in patients with poor-risk karyotype was independent from the mutation status. In summary, a poor-risk karyotype is an independent prognostic variable in advanced SM. Cytogenetic and molecular analyses should be routinely performed in all patients with advanced SM ± AHN because these investigations greatly support prognostication and treatment decisions.